Os Processos Territoriais de Inovação: A abordagem dos Sistemas de Inovação e a Perspectiva Transfronteiriça - Natário, Maria Manuela (2016)
The competitiveness of the territories depends on a great effort in innovation terms, what requests a solid national, regional and local innovation systems. The capacity of innovation of the border areas, specially of the Raia Central Ibérica, with economic reality of periphery space and of diffuse industrialization, it could start with the organization of the innovation system in a transborder perspective. Therefore, the aim of this paper is to characterize the innovation system on both sides of the border of the Raia Central Ibérica and to analyse how transborder systems of innovation works beginning with the identification of the main actors territorially integrated in the region and that in interaction could create synergies and a wider use of the local potentialities.